Criminal Profiling: the reality behind the myth (Indian Internet Journal of Forensic Medicine and Toxicology, 2010)
In contemporary criminology, with the advent of Criminal Profiling, criminal investigative procedure has changed dramatically. Various theories and methodologies of criminal profiling have been proposed e.g., FBI’s Crime Scene Analysis, Brent Turvey’s Behavioral Evidence Analysis, Canter’s Profiling Technique etc. It is certain that in near future, Criminal Profiling will play a decisive role in modern criminal investigation.
Keywords: criminal profiling; crime; behaviour; victim